2015
DOI: 10.1107/s139900471500259x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of ginseng major latex-like protein 151 and its proposed lysophosphatidic acid-binding mechanism

Abstract: Lysophosphatidic acid (LPA) is a phospholipid growth factor with myriad effects on biological systems. LPA is usually present bound to animal plasma proteins such as albumin or gelsolin. When LPA complexes with plasma proteins, it binds to its cognate receptors with higher affinity than when it is free. Recently, gintonin from ginseng was found to bind to LPA and to activate mammalian LPA receptors. Gintonin contains two components: ginseng major latex-like protein 151 (GLP) and ginseng ribonuclease-like stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…showed GLP151 protein could function as a carrier/transporter of LPA and deliver it to LPA receptors [20]. The present study provides additional information showing that gintonin might be a main regulator of ginseng-induced gliotransmitter release by acting on astrocytes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…showed GLP151 protein could function as a carrier/transporter of LPA and deliver it to LPA receptors [20]. The present study provides additional information showing that gintonin might be a main regulator of ginseng-induced gliotransmitter release by acting on astrocytes.…”
Section: Discussionmentioning
confidence: 91%
“…The recent elucidation of the three-dimensional structure of GLP151, a protein component of gintonin, revealed how it binds to LPA. The phosphate head group of LPA binds to imidazole ring histidine residues at the C-terminal of GLP151 with hydrogen bonds and acyl-chains of LPA bind to another portion of GLP151 [20]. In addition, they Time course of gintonin-mediated glutamate release.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study showed how GLP151 protein as a protein component of gintonin binds to LPA through the elucidation of three-dimensional structure of GLP151. The phosphate group of LPA binds to the imidazole ring of histidine residues at C-terminal of GLP151 with hydrogen bonds and acyl-chain of LPA interacts with other amino acids though hydrophobic interactions of GLP151 ( Choi et al, 2015b ). GLP151 protein was identified as a first plant-derived carrier or transporter of LPA, and deliver LPA to cognitive LPA receptors ( Choi et al, 2015b ).…”
Section: Discussionmentioning
confidence: 99%
“…Pyrabactin-resistant protein-like proteins (PYLs) [maximal score for Arabidopsis thaliana PYL10 (31)] are intracellular receptors for a plant hormone, abscisic acid (ABA). Ginseng major latex-like protein 151 (MLP151), which is thought to be associated with lysophosphatidic acid regulation, is a member of the PR-10/Bet v 1-type plant allergens (32, 33). ZhuI of Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%